2010
DOI: 10.1016/s1413-8670(10)70047-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards the complete eradication of mother-to-child HIV/HBV coinfection at Saint Camille Medical Centre in Burkina Faso, Africa

Abstract: The coinfection of HIV and hepatitis B virus (HBV) and their vertical transmission constitute a public health problem in sub-Saharan countries of Africa. The objectives of this research are: i) identify the pregnant women that are coinfected by HIV and HBV at Saint Camille Medical Centre; ii) use three antiretroviral drugs (zidovudine, nevirapine and lamivudine) to interrupt the vertical transmission of HIV and HBV from infected mothers; and iii) use the PCR technique to diagnose children who are vertically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…In addition to coinfections ( 21 , 22 ) and late treatment ( 20 ), the emergence of resistant HIV strains to ARV drugs resulting in high viral load is also an important factor in HIV vertical transmission. Furthermore, although the sample size is limited, in our study we found that the transmission rate is higher among women with a low rate of CD4 and high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to coinfections ( 21 , 22 ) and late treatment ( 20 ), the emergence of resistant HIV strains to ARV drugs resulting in high viral load is also an important factor in HIV vertical transmission. Furthermore, although the sample size is limited, in our study we found that the transmission rate is higher among women with a low rate of CD4 and high viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Full eradication of HBV transmission in highly viremic women may be achieved using additional interventions such as providing anti-HBV active drug(s) during the third trimester of pregnancy to decrease HBV DNA load of either wild-type or variants virus. 33–35 …”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa HIV-1/HBV frequency varies from 0 % to >28.4 % [ 8 , 9 ]. HIV-1 infection has been associated with a high prevalence of HBV infection in Burkina Faso [ 10 , 11 ]. Co-infection of HIV-1 and HBV is due to the common routes of transmission and increases the morbidity and mortality of the two infections.…”
Section: Introductionmentioning
confidence: 99%